Crystal-chemical controls on trace element partitioning between garnet and anhydrous silicate melt - van Westrenen, W; Blundy, J; Wood, B (1999)
We performed experiments at 3.0 GPa and 1530-1565 °C to investigate the effects of crystal composition on trace element partitioning between garnet and anhydrous silicate melt. Bulk compositions along the pyrope (Py: Mg3Al2Si3O12)-grossular (Gr: Ca3Al2Si3O12) join, doped with a suite of trace elements (Li, B, K, Sc, Ti, Sr, Y, Zr, Nb, Cd, In, REE, Hf, Ta, Th, and U) produced homogeneous garnets, ranging in composition from Py84Gr16 to Py9Gr91, in equilibrium with melt. Trace element partition coefficients (D-values), measured by SIMS, depend greatly on the Mg/(Mg + Ca) of garnet. For example, from Py84 to Py9, D(La) increases from 0.004 to 0.2, whereas D(U) increases from 0.029 to 0.42. These variations can be explained by the lattice strain model of Blundy and Wood (1994), which describes trace element partitioning of an element i in terms of the ionic radius of i (r(i)), the size of the lattice site on which i partitions (r0), the Young's modulus of the site (E), and the (theoretical) partition coefficient D0 for an ion of radius r0. For trivalent cations substituting in the garnet X-site (Y, REE, Sc, and In), apparent values of r0 fitted to our data vary systematically from 0.935 ± 0.004 Å (Py84) to 0.99 ± 0.01 Å (Py9), a trend consistent with variations in the size of the X-site. Values of D0 show an increase from Py9 (D0 = 2.8 ± 0.1) to Py84 (4.8 ± 0.1) and Young's modulus E varies from 257 ± GPa for Py60 to 590 ± 40 GPa for Py84. These results allow a quantitative assessment of the influence of crystal chemistry on garnet-melt D-values, thereby forming the basis for a predictive model similar to that recently developed for clinopyroxene-melt partitioning by Wood and Blundy (1997). Our new data emphasize the importance of taking into account crystal composition when modeling trace element behavior in natural systems.